Early detection of Breast cancer - Ramadan, Isra’a; Rawajbeh, Wala’a; Shtayeh, Haneen (My University, 2018)
Breast cancer detection is one of the most important problem in health care as it is the second most frequent cancer according to women. Early detection can significantly reduce the more mortality rate. it has been recently proposed that microwave imaging could be used as a cheaper and saver alternative to the commonly used combination of mammography. In our project we research about an alternative which is breast cancer detection using microwave imaging. In the first part we tried to design an antenna to radiate a signal into human body and the reflected signal from the body would be analyzed by the finite difference time domain(FDTD) numerical 1D,2D and 3D techniques which is depend on Maxwell's equation analysis that explores if there's a tumor or not. The project can be divided into two different parts. The first part presents a brief overview of UWB technology and explores its fundamentals, including UWB definition, summary of key UWB antenna concepts, as well as system and network advantages and limitations and its applications.Then it begins by assigning the explanation about Micro-Strip Patch antenna, including its basic characteristics, method of analysis, as well as the advantages and drawbacks of this type of antennas and finally how to design such antenna to operate at a certain frequency.